The Phenomenon of Fatherlessness in Families in the Concept of Love from the Perspective of Al Ghazali and St. Agustinus - Cinta Aulia Rienda Putri; M. Maulana Mas'udi; Mukayat Al-Amin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This study discusses the phenomenon of Fatherlessness, defined as the absence of a father figure either physically or emotionally, which significantly affects a child’s psychological, social, and spiritual development. Using a qualitative method through a library research approach, this article examines the concept of love from the perspectives of Al-Ghazali and St. Augustine as a philosophical response to the effects of Fatherlessness. Al-Ghazali emphasizes the concept of mahabbah in Sufism, viewing love as a means of purifying the soul and drawing closer to God. St. Augustine introduces ordo amoris, the proper order of love, in which love for God must be prioritized as the path to true happiness. Both thinkers assert that transcendental love toward God can spiritually compensate for the absence of a father figure. The findings show that such a religiously rooted approach to love may help individuals develop emotional resilience and spiritual balance. Thus, their philosophies offer a relevant alternative framework for understanding and addressing the impacts of Fatherlessness in the modern era.